IMPLEMENTATION OF DECISION SUPPORT SYSTEM WITH SMART METHOD IN GIVING RECOMMENDATIONS FOR DETERMINING THE BEST HANDPHONE - Nursucika Hasanah; William Ramdhan; Rohminatin (Informatika, Universitas Jenderal Soedirman, 2022)
During this pandemic, the need for mobile phones is increasing, especially in education. However, social circles are also increasing because all activities are mostly on cellphones. The many types of cellphones at this time have resulted in many consumers who are confused about buying a cellphone according to what they want. In addition, there are also consumers who want a cellphone with high / good specifications but at an affordable price. In the sale of cellphones, it was found that consumers had difficulties with the desired product, namely the many types of cellphones with the latest specifications, consumers wanted cellphones with good specifications and low prices. Then a decision-making system was made at the Joint Celluler store to assist in determining the best cellphone according to consumer needs. The research method used in this study is a quantitative research method by applying the SMART (Simple Multi Attribute Rating Technique) method of SPK, which is a multi-attribute decision-making method. This multi-attribute decision-making technique is used to support decision-makers in choosing between several alternatives. Therefore, a Decision Support System was built to determine the best cellphone so that the process of selecting a cellphone is more effective and makes it easier for consumers to get the cellphone they want. So that the application of the SMART method is able to produce decisions that are free from leadership interference in the selection of the best cellphone and will be more objective.